STRATEGI PENCEGAHAN DAN PENANGANAN KELUHAN NYERI PUNGGUNG BAWAH BERBASIS LINGKUNGAN PADA KARYAWAN RUMAH SAKIT ERIA BUNDA PEKANBARU - Mela Ardeline; Dedi Afandy; Ridwan Manda Putra (Jurnal Ilmu Lingkungan, 2021)
The work environment is closely related to the circumstances surrounding the activities of workers in doing their jobs. The office is a work environment where almost all the workers work mainly in a sitting position. Low back pain is one of the common occupational diseases of the workers. One of the risks of the increasing low back pain cases in workers is taking for granted the right work attitude, the location of the table and the size of the chair that is not ergonomic. RSIA Eria Bunda is one of the most visited RSIA by the public. The results of the initial observations at RSIA Eria Bunda found irregularities in work attitudes and the sitting positions of the employees and their work facilities were also not in accordance with the existing regulations. This is the reason the researcher conducted this research at RSIA Eria Bunda with the aim of knowing what factors can cause low back pain and what strategies can be used in handling complaints of low back pain in employees. The factors used in this study are individual and environmental factors and ergonomics. This research is conducted through quantitative approach with a survey method, cross-sectional data collection, low back pain questionnaire and RULA Worksheet to determine the employee's work attitude. Likewise, interviews and field observations are also conducted. Afterwards, determine the management strategy for complaints of low back pain with a SWOT Analysis. The results of the study are the following: First, there are complaints of low back pain in employees as 20 people (58,82%) and the most influencing factor is the work attitude (p = 0,022). Then, for the results of the RSIA SWOT Analysis, Eria Bunda is in a strong internal position and responds to existing opporto avoid threats. The strategy used by SO is to create a K3 evaluation team, improve the system and work environment and provide education about low back pain as a treatment strategy.